KLIMAKTERIUM: KLIMACTERIUM - maya rafida maya rafida (Surabaya Biomedical Journal, 2022)
Background: Menopause is a condition in which women experience physiological failure of ovarian function, as a result of the loss of activity of the ovarian follicles. Menopause is the stage when a woman's menstrual bleeding stops. At the age of 50 years, women enter menopause so that there is a decrease or loss of the hormone estrogen which causes women to experience complaints or disorders that often interfere with daily activities and can even reduce their quality of life. Objectives: to determine risk factors, pathophysiology, clinical manifestations, diagnosis and management of climacteric. Methods: collecting and analyzing journals using pubmed search media, google scholar, NCBI, ScienceDirect with keywords Conclusion: The climacteric phase consists of premenopause, perimenopause, menopause and postmenopause phases. The premenopause phase is the period for 4-5 years before the onset of menopause. This phase begins when a woman is 40 years old, characterized by irregular, prolonged menstrual cycles, little or a lot of menstrual blood, and sometimes accompanied by pain. The perimenopause phase is a transitional phase between pre-menopausal and postmenopausal. This phase is characterized by irregular menstrual cycles and levels of Follicle Stimulating Hormone (FSH), luteinizing hormone (LH), and highly variable estrogen (normal, high, or low). The menopausal phase is the condition of women who have no longer menstruating calculated after 12 months from the last menstruation, which is characterized by blood FSH levels >35 mIU/ml and estradiol levels <30 pg/ml.